Competent pedagogical leadership (Journal of Parents and Teachers, 2014)
Following the results of the PISA reports, where the level of Spain is below the European average, the debate is opened on whether teachers have little knowledge of their subjects and on whether people with better grades and more knowledge Can access to study Education.
Keywords: PISA reports; teachers; debate; Education.